Toxicity of bisphenol A (BPA) and its analogues BPF and BPS on the free-floating macrophyte Salvinia biloba - Santos, Jaqueline da Silva; Pontes, Montcharles da Silva; de Souza, Matheus Bispo [UNESP]; Fernandes, Simone Yasuda; Azevedo, Ricardo Antunes; de Arruda, Gilberto José; Santiago, Etenaldo Felipe (Elsevier, 2023)
Evidence linking the toxicity of bisphenol A (BPA) to environmental and public-health issues has led to restrictions on its use. This compound has been gradually replaced with analogues proposed as a safer alternative, normally bisphenol F (BPF) and bisphenol S (BPS), but these substitutes are structurally almost identical to BPA, suggesting they may pose similar risks. The effects of BPA and these analogues were compared for antioxidant activity, lipid peroxidation, free-radical generation, photosynthetic pigments, and chlorophyll fluorescence in Salvinia biloba Raddi (S. biloba) plants exposed to environmentally relevant and sublethal concentrations (1, 10, 50, 100 and 150 μM). Bisphenol exposure promoted alterations in most of the physiological parameters investigated, with BPS toxicity differing slightly from that of the analogues. Furthermore, S. biloba removed similar levels of BPA and BPF from aqueous solutions with ≈70% removed at the 150 μM concentration, while BPS was less effectively removed, with only 23% removed at 150 μM. These findings show that high concentrations of bisphenols (10≥) are toxic to S. biloba, and even typical environmental levels (≤1 μM) can induce metabolic changes in plants, bringing to light that both BPA and its substitutes BPF and BPS pose risks to aquatic ecosystems.
Keywords: Antioxidant defense; Chlorophyll fluorescence; Phytotoxicity; Plant metabolism; Reactive oxygen species